Akselerasi Inovasi Digital UMKM dengan Pemanfaatan Canva untuk Branding & Inovasi Berkelanjutan (SDGs 9) - Stanny Dewanty Rehatta; Inkreswari Retno Hardini; Ariska Novianti; Regina Humaningtyas Purba (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
Indramayu Regency holds significant economic potential through its Micro, Small, and Medium Enterprises (MSMEs) sector. However, the majority of MSME actors still face challenges in branding and digital marketing, mainly due to low awareness, limited graphic design skills, and restricted access to digital training. These issues have resulted in weak product competitiveness in both national and global markets. This community service program aims to enhance the digital skills of MSME actors through training on the use of Canva to create attractive and professional promotional materials. The program consists of four main stages: (1) preparation and MSME mapping, (2) socialization and Canva training, (3) monitoring and evaluation of training outcomes, and (4) reporting and follow-up recommendations. The results show a significant improvement in participants’ ability to independently design product visuals and a better understanding of the importance of digital branding. In addition to empowering MSMEs, the program also involves students in the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) initiative, contributing to the achievement of the university’s Key Performance Indicators (IKU). This program aligns with SDG 9, which focuses on industry, innovation, and infrastructure, and it has the potential to be replicated in other regions to support sustainable digital transformation for MSMEs.